Who benefits when coupons are issued by a duopoly from an e‐market?. (30th March 2021) - Lv, Hongjun
Abstract : This study examines a two‐dimensional differentiation model of both vertical product preferences and horizontal coupon preferences and investigates how couponing affects firms' promotion strategies and profits. The results show that when e‐coupons are issued by Firm 1, Firm 2's equilibrium profit increases with Firm 1's cost. Given e‐coupon issued by both firms, equilibrium profits decrease in Firm 1's cost and increase with Firm 2's cost, respectively. To carry out coupon strategies, there exist lose–win, win–win, and lose–lose scenarios, depending on firms' costs. Our study can be used in many online shopping platforms, giving them a noteworthy basis for decision making.